β-glucan induced trained immunity enhances antibody levels in a vaccination model in mice. - Jainu Ajit; Qing Chen; Trevor Ung; Matthew Rosenberger; Jeremiah Kim; Ani Solanki; Jingjing Shen; Aaron P Esser Kahn (PLoS ONE)
Trained immunity improves disease resistance by strengthening our first line of defense, the innate immune system. Innate immune cells, predominantly macrophages, are epigenetically and metabolically rewired by β-glucan, a fungal cell wall component, to induce trained immunity. These trained macrophages exhibit increased co-stimulatory marker expression and altered cytokine production. Signaling changes from antigen-presenting cells, including macrophages, polarize T-cell responses. Recent work has shown that trained immunity can generally enhance protection against infection, and some work has shown increased protection with specific vaccines. It has been hypothesized that the trained cells themselves potentially modulate adaptive immunity in the context of vaccines. However, the mechanistic link between trained immunity and subsequent vaccinations to enhance antibody levels has not yet been identified. We report that trained immunity induced by a single dose of β-glucan increased antigen presentation in bone-marrow-derived macrophages (BMDMs) and CD4+ T cell proliferation in-vitro. Mice trained with a single dose of β-glucan a week before vaccination elicited higher antigen-specific antibody levels than untrained mice. Further experiments validate that macrophages mediate this increase. This effect persisted even after vaccinations with 100 times less antigen in trained mice. We report β-glucan training as a novel prophylactic method to enhance the effect of subsequent vaccines.